2009
DOI: 10.1089/thy.2008.0116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Molecular Analysis of Thyroid Hypoplasia: A Population-Based Approach in Southern Brazil

Abstract: The prevalence of CH was within the previously reported range of 1:3000-4000. Ectopy was the most common etiology. Clinical analysis revealed distinct hormonal patterns in TH subgroup when compared with other variants of TD, with genetic abnormalities identified only in few cases in the TSH-R, PAX8, and NKX2.5 genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 33 publications
5
25
1
2
Order By: Relevance
“…THA results in congenital hypothyroidism only sporadically, which is detected by TSH neonatal screening (20). On the other hand, it has been observed that people with THA have significantly higher TSH and FT 3 concentrations when compared to those with fully developed thyroid, which is in accordance with our observations and suggests an impaired functional reserve of the unilobate thyroid (6).…”
Section: Discussionsupporting
confidence: 91%
“…THA results in congenital hypothyroidism only sporadically, which is detected by TSH neonatal screening (20). On the other hand, it has been observed that people with THA have significantly higher TSH and FT 3 concentrations when compared to those with fully developed thyroid, which is in accordance with our observations and suggests an impaired functional reserve of the unilobate thyroid (6).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, PAX8 and TTF1 synergistically activate the promoter of human TG (3). So far, 13 different mutations in the PAX8 gene have been reported (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), and the phenotypes of affected individuals vary considerably. Even within the same family, heterozygous individuals with PAX8 mutations can have no thyroid gland abnormality, have thyroid hypoplasia or TD (6), making it very difficult to identify individuals harboring a PAX8 gene mutation (1).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there have been reports of families with multiple affected cases and molecular biology studies have demonstrated the involvement of genes (TTF1 and 2, PAX8, TSH-R), which encode highly conserved transcription factors that result in agenesis, ectopia and thyroid hypoplasia, when inactivated (27,28).…”
Section: Discussionmentioning
confidence: 99%